The influence of maturity to parenthood on fertility intention among Malaysian childless married couples: Examining the moderating role of gender - Chew, En Jee; Yong, Wen Hui (2025)
As fertility rates continue to decline globally, understanding the psychological factors influencing individuals’ fertility intentions becomes increasingly important. This study aimed to examine how different dimensions of maturity to parenthood—valence, behavioural, and cognitive-emotional—predict fertility intention, and whether gender moderates these relationships. A quantitative, cross-sectional research design was employed. Participants were recruited through non-probability sampling methods, including purposive, self-selection, and snowball sampling, resulting in a sample of 95 married individuals, currently childless, aged between 20 and 44 years (M = 31.23, SD = 5.25). Most participants were female (n = 71), followed by male (n = 24). The study was conducted in Malaysia, and data were collected via online self-report surveys. Instruments included the Desire to Avoid Pregnancy Scale, assessing fertility intention and the three subscales of the Maturity to Parenthood Scale. Data were analysed using SPSS, including Pearson correlation analysis, hierarchical multiple regression analysis and Hayes’s PROCESS macro (Model 1). Results indicated that behavioural maturity significantly predicted fertility intention, whereas valence and cognitive-emotional maturity did not. Gender did not moderate the relationship between any maturity dimensions and fertility intention. These findings suggest that psychological maturity, particularly practical preparations, is more strongly related to fertility intention than valuing parenthood or holding realistic and emotionally grounded attitudes. No gender moderation may reflect shifting gender roles and shared practical and relational considerations, as well as similar viewpoints in family planning across genders. This study provides useful implications for fertility education, reproductive health interventions, and policymaking that promote earlier behavioural readiness toward parenthood.